Linguistic Bibliography for the Year 2002 and Supplement for previous years - Шмігер, Т. (Мовознавство, 2010)
Відгук на зведену бібліографію європейської мовозначної літератури: LINGUISTIC BIBLIOGRAPHY FOR THE YEAR 2002 AND SUPPLEMENT FOR PREVIOUS YEARS / Ed. by S. Tol and H. Olbertz with the assistance of P. van Beest and Th. Horstman.— Dordrecht, Springer, 2006.— CVIII, 1445 p.— (Permanent International Committee of Linguists).